Fungsi Hukum Pidana Terhadap Pembukaan Paksa Road Barrier oleh Supeltas di Bandar Lampung - Silvia Kirani; Eko Raharjo; Fristia Berdian Tamza (Lembaga Pengembangan Kinerja Dosen, 2025)
Traffic congestion in Bandar Lampung City has led to the emergence of volunteer traffic controllers, commonly known as Pak Ogah. Their presence has sparked mixed reactions from the public. Some view them as helpful in maintaining traffic flow in the absence of traffic police, while others consider their actions to cause disturbances, traffic jams, and illegal levies. One of the most controversial actions is the forced opening of road barriers without proper authorization and outside the scheduled times, which violates Law Number 22 of 2009 on Road Traffic and Transportation. This study addresses two main issues: the functionalization of criminal law against Supeltas (volunteer traffic controllers) who unlawfully open road barriers, and the policies of the traffic police (Polantas) regarding their presence. This research uses normative and empirical juridical methods, with data collected through literature studies and field interviews with four key informants. The findings reveal that such actions constitute legal violations that can jeopardize road safety and public order. Firm legal enforcement is essential, yet specific regulations concerning Supeltas are still lacking. This study recommends guidance and supervision by law enforcement, particularly traffic police, and the application of criminal sanctions in accordance with existing legal provisions.